Implementation of the Wafa Method in Taḥsīn Qirāʾah al-Qurʾān at SMP Insan Cendekia Madani - Muamar, Muamar; Said, Hasani Ahmad; Suwendi, Suwendi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
The need for effective and engaging Qur’anic learning methods has led to the adoption of various pedagogical innovations in Islamic education. This study aims to analyze the implementation of the Wafa method—integrating the Gharib book, Quantum Teaching approach, TANDUR learning model, and Wafa Tilawah application—in enhancing students’ tajwid and Qur’anic recitation (Taḥsīn Qirāʾah al-Qurʾān) at SMP Insan Cendekia Madani, Serpong. Using a qualitative case study approach, data were collected through observation, interviews, and document analysis. The findings were examined narratively and validated using triangulation techniques to ensure credibility from multiple sources. The results show that the Wafa method is effectively implemented through a multi-sensory approach involving visual, auditory, and kinesthetic modalities. Key success factors include competent teachers, diverse learning media, adequate infrastructure, and a supportive school culture. However, limitations such as varying student abilities and time constraints necessitate more individualized learning strategies. The novelty of this study lies in its integrative examination of the Wafa method with contemporary pedagogical frameworks in a formal school setting, which is still underexplored in Indonesian Islamic education literature. This study suggests that the Wafa method is not only effective in improving students’ Qur’anic recitation skills but also adaptable for broader implementation in similar educational contexts.